Design and simulation of low power CMOS oscillator for MEMS saw resonator - Jamilah binti Karim
Fully integrated transceiver on silicon is the future of today's wireless system as this solution will reduce the cost, size and power consumption. Fully integrated transceiver can be realized by using microelectromechanical systems (MEMS) based oscillators. MEMS based oscillators' offers several advantages such as small size, low cost and capable to be fully integrated. This work presents the design, simulation and measurement of an oscillator for a surface acoustic wave (SAW) MEMS resonator. The design process begins by first extracting the RLC parameter for resonators using AWR®Microwave software. Pierce oscillator circuit topology was chosen since it is simpler and provides straightforward biasing. The oscillators' transistors were designed to provide continuous and stable oscillation at 868MHz, 915MHz and 2.5GHz. The circuits were simulated in MIMOS 0.35μm CMOS technology process via Cadence virtuoso software. The designed is sent to MIMOS for fabrication in FAB2 0.35μm AMS CMOS 3.3V technology process. The fabricated oscillator circuit's open loop gain is 17.5dB and consumes 3mW power. When integrated with the SAW resonator, the device demonstrated phase noise of -84.6dBc/Hz at 100kHz offset frequency. The far from carrier noise is -103dBc/Hz. This result is comparable to the current MEMS oscillators. This work indicates that MEMS-based oscillators have high potential for integration with modern wireless systems.